In Vivo Confocal Microscopic Evaluation of the Limbus and Cornea in Vogt Koyanagi Haradas Syndrome. (18th August 2022) - Thundikandy, Radhika; Priya Chidambaranathan, Gowri; Radhakrishnan, Naveen; S. R, Rathinam
ABSTRACT: Aim: To elucidate the microarchitecture of limbus and cornea in subjects with Vogt Koyanagi Haradas syndrome (VKH) Methods: From January 2019 to December 2019 a total of 17 VKH subjects, 5 acute and 12 chronic, 18 non VKH uveitis controls, and 6 healthy controls were recruited for this study . In vivo confocal microscopic (IVCM) analysis of the limbal basal epithelium, scleral side of the limbus, limbal niche, corneal keratocytes, and corneal nerves was carried out . Results: Absence of pigmented cells in the limbal basal epithelium, presence of inflammatory cells on the scleral side of the limbus, fibrotic niche, degenerated keratocytes, thinning, and beading of corneal nerves were noted in VKH eyes as compared to controls. Conclusion: Presence of inflammatory cells and depigmentation of limbus in chronic VHK points to disease progression.Keratocyte and corneal nerve changes in Vogt Koyanagi Haradas syndrom are novel findings.